(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
his article presents a comprehensive analysis of the socio-philosophical dimensions of local customs, traditions, and rituals in Uzbek society. The introduction addresses the balance between national values and traditions within the context of globalization. The study employs philosophical-analytical, historical-genetic, comparative, and explanatory anthropological methods in an integrated manner, drawing on sources including Bahodir Sarimsakov, Mahmud Sattor, Adham Ashirov, Usmon Khosil, and Rtveladze. Customs, as systems of social norms, introduce informal regulations to societal behavior. Customs and rituals provide meaning that supports cultural and spiritual stability. Rituals, as a collective symbolic-practical system, implement integration, strengthening the personality, education and upbringing, and moral norms. Historical analysis shows the changes in customs and rituals from the Zoroastrian and agrarian rituals to the Islamic era, Soviet secularization, independence and modern globalization. The article analyzes the compatibility of the theories of Durkheim, Mauss, Malinovsky and Giddens. The article reveals the functioning of customs and rituals as a spiritual bond between society and the individual through an approach that is combined with the views of Eastern thinkers Farabi, Beruni and Navoi.